Activity Budget And Space Utilization Of Captive Bornean Orangutan - Zainol, Muhammad Zaki (2017)
Endemic to Malaysia and Indonesia, Bornean Orangutan (P. pygmaeus) was declared to be critically endangered in 2016 because of extensive deforestation and other human caused pressures. Rescued orangutans were sent to rehabilitation centers and those that unable to be release will be occupying captive centers i.e. zoo. The orangutans that unable to be released could be utilized as educational subject on wildlife learning. Hence, it is crucial to preserve orangutan natural behavior. Proper designed enclosure including suitable social group and intensive care must be provided to make this happen. This study was carried out to determine captive orangutan activity budget, space utilization and to study what are the captivity worker’s motivational factors.